Solid Substrate Fermentation Of Rice Straw By Trichoderma Viride IBRL-TCS06 For Fermentable Sugars Production - Teoh , Chai Sin (2011)
The research focused on the production of fermentable sugars in solid substrate fermentation (SSF). The potential use of rice husk and rice straw as substrates were used to screen for potential microorganism that capable of producing fermentable sugars under SSF. Five types of fungi were used, namely Aspergillus niger USM AI-I, A. niger USM AI-II, A. niger USM AI-F4, Trichoderma viride IBRL-TCS06 and Phanerochaete chrysosporium, either as a single or mixed cultures. Results showed that Trichoderma viride IBRL-TCS06 was efficient in degrading rice straw and producing the highest fermentable sugars approximately 18.13 ±0.67 mg/g substrate with the fungal growth of 1.46±0.08 mg glucosamine/g substrate under condition of 5 g of 0.75 mm substrate,